2011
DOI: 10.4061/2011/417635
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Tuberculosis and Its Histological Pattern in Patients with Enlarged Lymph Node

Abstract: Settings. Tuberculosis is a major health problem in the Republic of Yemen. Tuberculous lymphadenitis is one of the most common forms of extrapulmonary tuberculosis. Therefore, this retrospective descriptive study was conducted in Yemen to investigate the morphological pattern of tuberculous lymphadenitis, as well as to assess the reliability measures of (ZN) Ziehl-Neelsen and fluorescent methods in identification of Mycobacterium tuberculosis. Methodology. One hundred lymph nodes tissue biopsies that were prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 11 publications
(13 reference statements)
6
26
2
2
Order By: Relevance
“…Given the high prevalence of tuberculosis in Low income settings, most of these patients are likely to be treated with antituberculosis medication and an alternative diagnosis is only sought when there is no response several months later. [25][26] However, our median patient and physician delays for Hodgkin lymphoma patients were not extremely long compared to other types of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Given the high prevalence of tuberculosis in Low income settings, most of these patients are likely to be treated with antituberculosis medication and an alternative diagnosis is only sought when there is no response several months later. [25][26] However, our median patient and physician delays for Hodgkin lymphoma patients were not extremely long compared to other types of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis was confirmed by (i) scrape smears from the basal meninges of the brain positive for acid fast bacilli (AFB); (ii) positive antibodies/immunocomplexes in CSF against MTB by ELISA; (iii) CSF culture positive for MTB; (iv) granulomatous meningitis on histological examination with or without demonstrable AFB in histological sections by Ziehl Neelsen's staining [35]. All cases were positive for HIV-1 on serological testing and confirmed to be HIV-1 clade C by clade specific PCR developed at Jawaharlal Nehru Centre for Advanced Scientific Research, Bangalore and validated [36].…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, stains for tuberculosis are often particularly challenging for pathologists. In a study of 100 cases of tuberculous lymphadenitis diagnosed by conventional histopathology, only 3 (3%) were found to be positive by Ziehl-Neelsen staining, indicating a very low sensitivity [9]. Furthermore, smears of cultured Mycobacterium tuberculosis revealed that the sensitivity of acid-fast stains (Ziehl-Neelsen and rhodamine-auramine staining) drastically decreased following formalin treatment or combined formalin and xylene treatment when compared with untreated smears [10].…”
Section: Introductionmentioning
confidence: 94%